2016
DOI: 10.1111/nan.12328
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes of patients with amyotrophic lateral sclerosis linked to gene mutations display altered TDP‐43 subcellular distribution

Abstract: In ALS forms characterized by TDP-43 mislocalization in motor neurons, monocytes display this alteration, even when not manifest in CLM. Monocytes may be used to support diagnosis, as well as to identify subjects at risk, of ALS and to develop/monitor targeted treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…Interestingly, our study revealed that ALS MDMi recapitulated de novo TDP-43 aggregates and increased phospho-TDP-43 immunoreactivity, which are major hallmarks of ALS. These observations further support the growing evidence for TDP-43 pathology in microglia (Paolicelli et al, 2017), and other non-neuronal cell types including skin fibroblasts (Riancho et al, 2020), circulating lymphomonocytes, and in monocytes/macrophages from a subgroup of ALS patients (De Marco et al, 2017; De Marco et al, 2011). Our study is the first to report the appearance of abnormal TDP-43 pathology in microglia generated from people living with ALS.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, our study revealed that ALS MDMi recapitulated de novo TDP-43 aggregates and increased phospho-TDP-43 immunoreactivity, which are major hallmarks of ALS. These observations further support the growing evidence for TDP-43 pathology in microglia (Paolicelli et al, 2017), and other non-neuronal cell types including skin fibroblasts (Riancho et al, 2020), circulating lymphomonocytes, and in monocytes/macrophages from a subgroup of ALS patients (De Marco et al, 2017; De Marco et al, 2011). Our study is the first to report the appearance of abnormal TDP-43 pathology in microglia generated from people living with ALS.…”
Section: Discussionsupporting
confidence: 82%
“…Further evidence of TDP-43 spreading comes from the higher levels of free and exosomal TDP-43 identified in the CSF of ALS patients compared to control groups (Kasai et al , 2009; Sproviero et al , 2018). TDP-43 aggregates were also discovered in serum leucocytes from ALS patients (Foulds et al , 2008, 2009; Corrado et al , 2009; De Marco et al , 2011, 2017; Verstraete et al , 2012; Alquezar et al , 2016). Although pathological TDP-43 has the property to penetrate nearby cells, it remains unclear as to how this phenomenon occurs.…”
Section: The Prion-like Characteristics Of Aggregated Tdp-43mentioning
confidence: 90%
“…There is now evidence of abnormal accumulation/location of these proteins in monocytes. For example, altered location of TDP43 in monocytes of patients with genetic mutations in TARDBP, the gene encoding TDP-43 has been demonstrated (111). There is also a report that C9orf72 is expressed in myeloid cells and that expression in monocytes increases after activation (112).…”
Section: Monocyte Numbers and Proportionsmentioning
confidence: 99%